IMPLEMENTASI AKTIVITAS FISIK OLAHRAGA JALAN KAKI MENGONTROL KADAR GULA DARAH PADA KELUARGA DENGAN DIABETES MELLITUS: STUDI LITERATUR - Yuli Astuti (Jurnal Medika Hutama, 2021)
Diabetes Mellitus is a metabolic disorder characterized by increased blood sugar levels that can cause damage to various systems of the human body. This literature study aims to examine the effects, methods and results of physical activity walking on controlling blood sugar in people with diabetes mellitus. This study uses a literature study, articles are obtained from 1 database, namely Google Scholar using inclusion and exclusion criteria. The keyword used in this literature search is “Diabetes Mellitus. Blood Sugar Levels. Walking” and “Diabetes Mellitus. Blood Glucose. Walking". From 10 studies, it was found that walking exercise has an effect on controlling blood sugar levels in people with diabetes mellitus. The average respondent decreased by 30 mg/dl. There is an effect of physical activity walking on controlling blood sugar levels with value = 0.000 <0.05. Physical activity walking can help people with diabetes mellitus control their blood sugar levels.